Impulse Buying: Pengaruh Price Discount dan Display Product pada Mall Ramayana Ciplaz Bandar Lampung - Sujarwo, Anton; Kristanto, Herry; Wimbawani, Wiwik (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2023)
ABSTRACT The purpose of this study was to determine the influence of price discounts and product displays on impulse buying at the Ramayana Ciplaz Mall in Bandar Lampung City. Impulse Buying can occur in any condition and in every human being. Someone who has a hobby of shopping will certainly not waste the situation that occurs if the factor of impulse buying is in front of their eyes, for example a discount. Someone will of course buy the product for reasons of economy. This study chose a quantitative method, the source of the data of which was obtained from a direct survey of respondents who visited Ciplaz Bandar Lampung. The research sample was 100 respondents. Multiple linear regression is the analysis technique chosen by the researcher. So that it produces Price Discount (X1) value Sign.0.004 <0.05, meaning that Price Discount (X1) has an effect on Impulse Buying. The higher and longer a product gets a discount, the higher the consumer will make unplanned purchases. Display Product (X2) value Sign.0.009 <0.05, meaning that Display Product (X2) has an effect on Impulse Buying. The more strategic and attractive a product is displayed, the more customers will make unplanned purchases.